Konseling Ibu Hamil pada Bidan Praktik Swasta dan Puskesmas di Kabupaten Bantul - Retno Heru; Mubasysyir Hasanbasri; Mohammad Hakimi (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Counseling for Pregnant Women at Midwife Practice and Community Health Center in Bantul DistrictBackground: One of the factors of Maternal and Neonatal Mortality is the lack of knowledge on the cause and how to deal with important complications during pregnancy, labor, and post natal. Counseling is an effort to dig and give useful information in order to help pregnant mother to take decisions. Midwife practice and Community Health Center is an organization which aims at giving service to pregnant mother including counseling. Midwife practice an independent organization which is managed privately, whereas Community Health Center is an organization which belongs and runs by the government. Objectives: The objective of the research is to find out the implementation of counseling on pregnant mother which includes, time, places, instruments, materials, problem solving, training efforts, and form of teaching counseling skill on midwife practice and Community Health Center in Bantul district. Method: Research method used in this research is qualitative research method with case study and descriptive method. The analysis unit is the pregnant mother, midwife in charge in midwife practice and in Community Health Center. The data was taken using purposive sampling through interview, observation and library study. Result: Counseling implementation in midwife practice and Community Health Service is done through giving information. The time done for counseling is under the standard which was below 20 minutes. The counseling process is undergone in one place along with the other services, and there are many patients in the room. The instruments used for counseling is just KIA book and there are no other instruments, the information given is merely on the problems which are shared by the pregnant mother. If the pregnant mother doesn’t share her problem, the midwife will not give counseling. The problem which is often faced by the midwife is that pregnant mother has difficulties in intrepreting information given. Problem solving is done through the participation of the husband during the counseling service. Training efforts to increase the counseling skill has not been done officially. The efforts taken so far is by reading books or learn from other coleagues. The form of teaching counseling skill is using roleplay, done in pairs and not more than 45 minutes. Conclusion: The implementation of counseling for pregnant mother is done inappropriately, which is not the same as it is stated in the Standart Service of Midwifery. It makes pregnant mother doesn’t have the necessary information dealing with the pregnancy.Keywords: Counseling, Pregnancy, MidwifeLatar Belakang: Salah satu penyebab tingginya Angka Kematian Bayi dan Angka Kematian Ibu adalah karena kurangnya pengetahuan tentang penanggulangan dan komplikasi-komplikasi penting dalam kehamilan, persalinan, dan nifas. Konseling adalah upaya menggali dan memberikan informasi guna mendapatkan apa yang dibutuhkan dan membantu ibu hamil dalam mengambil keputusan. Bidan Praktik Swasta dan Puskesmas adalah organisasi pelayanan kesehatan yang memberikan pelayanan pada ibu hamil termasuk konseling. BPS adalah organisasi pelayanan kesehatan swasta yang dikelola secara mandiri, sedangkan Puskesmas adalah organisasi pelayanan kesehatan yang di kelola oleh pemerintah. Tujuan: Tujuan penelitian ini adalah untuk mengetahui pelaksanaan konseling pada ibu hamil yang meliputi: praktik konseling, waktu, tempat, alat bantu, materi, cara mengatasi hambatan, upaya peningkatan ketrampilan, dan bentuk pengajaran ketrampilan konseling di pendidikan di BPS dan puskesmas di Kabupaten Bantul. Metode: Metode penelitian adalah metode kualitatif dengan rancangan studi kasus dan bersifat deskriptif. Unit analisis adalah ibu hamil, bidan pelaksana di BPS dan puskesmas. Data diambil secara purposive sampling melalui wawancara mendalam dan lembar pengamatan konseling serta penelusuran dokumen. Hasil: Praktik konseling di BPS dan puskesmas dalam bentuk pemberian informasi. Waktu yang digunakan dalam proses konseling masih kurang yaitu di bawah 20 menit. Tempat yang digunakan untuk proses konseling menjadi satu dengan tempat yang digunakan untuk periksa kehamilan, dan banyak orang yang ada dalam ruangan periksa. Alat bantu yang digunakan untuk konseling sebatas buku KIA dan belum menggunakan alat bantu yang lain. Informasi yang diberikan sebatas pada keluhan yang disampaikan oleh ibu hamil. Jika ibu hamil tidak menyampaikan keluhan, bidan tidak berusaha menggali permasalahan atau memberikan informasi. Hambatan yang paling sering ditemui bidan adalah sulitnya ibu hamil memahami informasi yang diberikan bidan. Cara penyelesaian hambatan dengan cara melibatkan suami dalam proses konseling. Upayapeningkatan ketrampilan konseling secara resmi seperti pelatihan-pelatihan belum ada. Upaya yang dilakukan selama  ini adalah dengan membaca buku-buku dan belajar dari teman. Bentuk pengajaran ketrampilan konseling di pendidikan dengan metode roleplay, dilaksanakan dikelas, dan dilakukan dengan teman sendiri. Kesimpulan: Proses konseling pada ibu hamil yang dilakukan oleh bidan pada umumnya tidak berjalan sebagaimana mestinya, yaitu tidak sesuai dengan pedoman yang ada dalam standar  pelayanan kebidanan. Dampaknya adalah ibu hamil belum paham dengan segala hal yang berkaitan dengan kehamilan.Kata Kunci: Konseling, Kehamilan, Bidan